ANALISIS PENGARUH PERUBAHAN ORGANISASI, KOMUNIKASI DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA PT PLN (PERSERO) APP CILEGON - Priyo Susilo; Arief Rahman (JMB : Jurnal Manajemen dan Bisnis, 2016)
This study aims to analyze how much influence organizational change, communication and work environment as the independent variables on employee performance. The object of the research is PT PLN (Persero) APP Cilegon using a study population that employees PLN APP Cilegon. The study concluded that partially are positive and significant effect of the variable changes in the organization, communication and working environment independently of the performance of employees at PT PLN (Persero) APP Cilegon, wherein the degree of influence of organizational change on employee performance medium category, while the influence communication and working environment on the performance of each employee including the strong category.